Quantum Codes from Cyclic Codes over A Class of Nonchain Rings - Sari, Mustafa; Siap, Irfan (IEEE, 2015)
Lately, quantum error correcting codes have been considered as the Gray images of some special codes over various rings [1], [4], [9]. In this study, we investigate the structure of the cyclic codes of arbitrary length over the finite nonchain ring R-p = F-p + vF(p) +... + v(p-1)F(p) where v(p) = v and obtain quantum error correcting codes over F-p by using the Gray map defined in [2].
Keywords: Engineering